Strategies for Using Visual Media in Handling Children with Down Syndrome in Non-Inclusive Early Childhood Education Environments - Hayati, Eni Nur; Slamet, Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Learning for children with Down syndrome in non-inclusive early childhood education (PAUD) institutions still faces challenges, primarily due to teachers' limited ability to provide adaptive learning media tailored to their characteristics. Although theory suggests that visual media is effective in supporting information processing for children with intellectual disabilities, its implementation in the field is less than optimal. This situation indicates a research gap, namely the lack of in-depth studies on strategies for using visual media in non-inclusive early childhood education contexts that lack specialized facilities or teacher training. This study aims to analyze strategies for using visual media in learning for children with Down syndrome and identify obstacles that arise in daily learning practices. The study used a descriptive qualitative approach with a purposive sampling technique involving classroom teachers, principals, and parents. Data were collected through lesson observations, in-depth interviews, and documentation of the RPPM (Learning Plan), RPPH (Learning Plan), and the visual media used. Data analysis followed the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and conclusion drawing. Data validity was strengthened through triangulation of sources and methods to enhance the credibility of the findings. The results showed that the use of visual media such as picture cards, posters, and concrete props improved attention, instruction comprehension, and communication skills in children with Down syndrome. Children responded better when information was presented visually than verbally. However, learning was still limited by minimal teacher training, limited resources, and the lack of systematic developmental evaluation instruments. This study contributes to the development of adaptive learning strategies in non-inclusive early childhood education (ECE) by confirming that the effectiveness of visual media is largely determined by teacher competence and institutional support.